Electronic modulation of a copper/zinc oxide catalyst by a heterojunction for selective hydrogenation of carbon dioxide to methanol. - Liao, F; Zeng, Z; Eley, C; Lu, Q; Hong, X; Tsang, S (2012)
Methanol from CO 2: For the hydrogenation of carbon dioxide, a marked increase in the methanol selectivity was observed when the reaction was catalyzed by Cu/rod-shaped ZnO/CdSe with heterojunction structure. Diffusion reflectance, photoluminescence, and ESR spectroscopies clearly indicated an increase in the electron density because of the incorporation of CdSe in the core-shell morphology of Cu/rod-shaped ZnO (see picture). Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.